2012
DOI: 10.1212/wnl.0b013e318259e2cf
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guideline update: Medical treatment of infantile spasms [RETIRED]

Abstract: Objective:To update the 2004 American Academy of Neurology/Child Neurology Society practice parameter on treatment of infantile spasms in children.Methods: MEDLINE and EMBASE were searched from 2002 to 2011 and searches of reference lists of retrieved articles were performed. Sixty-eight articles were selected for detailed review; 26 were included in the analysis. Recommendations were based on a 4-tiered classification scheme combining pre-2002 evidence and more recent evidence. Results:There is insufficient e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
285
3
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 292 publications
(311 citation statements)
references
References 40 publications
8
285
3
15
Order By: Relevance
“…A through critical review was published in 2004 by the American Academy of Neurology Central Nervous System group to provide guidelines to clinicians in the treatment of infantile spasms [15]. In a recent paper published in Neurology, the same group provides an update to these guidelines [7]. The researchers carried out database searches of MEDLINE and EMBASE for relevant studies conducted during the period 2002-2011, and place their findings in the context of pre-2002 evidence [15].…”
Section: What Is the Most Effective Treatment For Infantilementioning
confidence: 99%
See 4 more Smart Citations
“…A through critical review was published in 2004 by the American Academy of Neurology Central Nervous System group to provide guidelines to clinicians in the treatment of infantile spasms [15]. In a recent paper published in Neurology, the same group provides an update to these guidelines [7]. The researchers carried out database searches of MEDLINE and EMBASE for relevant studies conducted during the period 2002-2011, and place their findings in the context of pre-2002 evidence [15].…”
Section: What Is the Most Effective Treatment For Infantilementioning
confidence: 99%
“…An older, prospective, large Finnish study showed no difference in response rate (cessation of infantile spasms and resolution of hypsarrhythmia) or relapse rate comparing low-dose (20-40 IU/day) [N = 54] and high-dose (80-120 IU/day) [N = 97] regimens; however, long-term cognitive outcome was better with the low-dose regimen [29,30]. Recent evidence also suggests that low-dose ACTH is probably as effective as high-dose ACTH for short-term treatment of infantile spasms (Class I and II evidence) [7]. Therefore, the following recommendation was given in 2012: ''Low-dose ACTH should be considered as an alternative to high-dose ACTH for treatment of infantile spasms (Level B)'' [7].…”
Section: What Is the Most Effective Treatment For Infantilementioning
confidence: 99%
See 3 more Smart Citations